iTRAQ-Based Proteomic Analysis of Visual Cycle-Associated Proteins in RPE of rd12 Mice before and after RPE65 Gene Delivery - Qinxiang Zheng; Yueping Ren; Radouil Tzekov; Shanshan Hua; Minghan Li; Jijing Pang; Jia Qu; Wensheng Li (Journal of Ophthalmology)
Purpose. To investigate the iTRAQ-based proteomic changes of visual cycle-associated proteins in RPE of rd12 mice before and after RPE65 gene delivery. Mehtods. The right eyes of rd12 mice underwent RPE65 gene delivery by subretinal injection at P14, leaving the left eyes as control. C57BL/6J mice were served as a wide-type control group. ERGs were recorded at P42, and RPE-choroid-sclera complex was collected to evaluate the proteomic changes in visual cycle-associated proteins by iTRAQ-based analysis. Western blot was used to confirm the changes in the differentially expressed proteins of interest. Results. ERG parameters improved dramatically at P42 after RPE65 delivery. The proteomics analysis identified a total 536 proteins with a global false discovery rate of 0.21%, out of which 7 were visual cycle-associated proteins. RALBP-1, RBP-1, and IRBP were reduced in the untreated rd12 eyes and the former two were improved after gene therapy, confirmed by Western blot analysis. Conclusions. RPE65 gene delivery restored retinal function at P42 and modified the expression of other functional proteins implicated in the visual cycle. The level of RALBP-1 was still below the normal level after gene therapy in rd12 mice, which may explain the delayed dark adaption in LCA patients undergoing similar therapy.